Institutional innovations towards gender equity in agrobiodiversity management: collective action in Kerala, South India - Padmanabhan, Martina Aruna (International Food Policy Research Institute, 2005)
The maintenance of crop diversity on farmers’ fields in hot spots of plant genetic diversity is considered a ”global life insurance policy“ in the Convention on Biological Diversity (CBD 2001:1). This paper provides evidence of the importance of the contribution of poor women farmers to the conservation and utilization of plant genetic resources (PGR) for food and agriculture. As a consequence, its equitable recognition and economic reward is a key issue in the sustainable management of agrobiodiversity. The present investigation into the institutions governing PGR, with special emphasis on gender equity and collective action, focuses on the identification of innovative institutions with special focus on women’s interests. The paper considers empirical evidence from Kerala, a hot spot of biodiversity in India, investigates properties of local biodiversity resources, and the role of collective action in conservation. To help understand conservation and utilization of agrobiodiversity the investigation uses a combination of institutional and gender analysis. Keywords: gender; agrobiodiversity management; collective action; India; institutional change